Effect of chirality of L/D-proline and prochiral glycine as the linker amino acid in five-atom linked thymidinyl-(alpha-aminoacid)-thymidine dimers - Seema Bagmare; D'Costa, Moneesha; Kumar, Vaijayanti A. (Chemical Communications, 2009)
The chirality of the amide linker in dimer blocks was found to have a profound effect on the orientation of base stacking interactions as studied by CD and NMR spectroscopy.

Synthesis of all four nucleoside-based beta-amino acids as protected precursors for the synthesis of polyamide-DNA with alternating alpha-amino acid and nucleoside-beta-amino acids - Seema Bagmare; Varada, Manojkumar; Banerjee, Anjan; Kumar, Vaijayanti A. (Tetrahedron, 2013)
A simple approach is described for the synthesis of all four orthogonally protected nucleoside-beta-amino acids from commercially available starting materials. Synthesis of a model tetrameric DNA sequence in 5'-3'direction employing trityl strategy and glycine as alpha-amino acid alternating with nucleoside-beta amino acids is described. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Antisense therapeutics; Neutral DNA analogues; Nucleoside-beta amino acids

Glycine-linked nucleoside-beta-amino acids: polyamide analogues of nucleic acids - Banerjee, Anjan; Seema Bagmare; Varada, Manojkumar; Kumar, Vaijayanti A. (Bioconjugate Chemistry, 2015)
3'-5'-Deoxyribose-sugar-phoshate backbone in DNA is completely replaced by 2'-deoxyribonucleoside-based beta-amino acids interlinked by glycine to create uncharged polyamide DNA with 3'-5'-directionality. These oligomers as conjugates of alpha-amino acids and nucleoside-beta-amino acids bind strongly and sequence-specifically only to the antiparallel complementary RNA and DNA.

Investigation of the effect of amino acid chirality in the internucleoside linker on DNA:DNA and DNA : RNA duplex stability - Seema Bagmare; Gunjal, Anita D.; Kumar, Vaijayanti A. (Tetrahedron, 2015)
Enzymatically and chemically stable amide-linked di/oligonucleosides are highly desired synthetic targets in which the phosphodiester linkages in native DNA are replaced by amide linkers of appropriate length and stereochemistry. The five-atom amide-linked dimers, synthesized from 3'-amino-3'-deoxy thymidine, (alpha-(L/D) proline/prochiral glycine and thymidine/uridine-4'carboxylic acid derivatives, were incorporated into the DNA backbone to achieve partial replacement of selected phosphodiester linkages. The results stressed the importance of the chirality of linker amino acid. D-Proline was found to be the most compatible as an internucleoside linker in the DNA backbone to stabilize the complexes with DNA or RNA as compared to L-proline and glycine. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: alpha-Amino acid; Chiral amide linkage; DNA; Five-atom amide linkage; L/D-Proline